MENGEMBANGKAN REGULASI DIRI SISWA: IKHTIAR MENUJU TERBENTUKNYA KESADARAN MORAL DAN PRILAKU ADAPTIF SISWA - Moh. Mahfudz Faqih (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
One of the manifestation of globalization’s negative influences is the increase of maladaptive behavior among teenagers. Maladaptive behavior is a manifestation of the less skilful of teenagers in aspects of intrapersonal and / or interpersonal. One of the important things is self-regulation which is a systematic efforts to direct thoughts, feelings and actions towards the achievement of objectives. Moral awareness is a person's determination in a situation that contains moral content and legitimately can be considered from a moral point of view. On the other hand, adaptive behavior is a person's ability to harmonize and modify his/her behavior to fit the demands of such situations. Based on the theory of social cognition, it is assumed that self-regulation can increase the intensity of moral awareness and minimize maladaptive behaviors of students. Self-regulation of the student can be developed at school through integration into learning processes, and in family through habituation to pray regularly